Frenzy: A Platform for Friendsourcing - Chilton, Lydia; Cordeiro, Felicia; Weld, Daniel; Landay, James (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
Although micro-task crowdwork was popularized by the Mechanical Turk (MTurk) labor-market platform, it is useful in many other contexts and communities as well. Unfortunately, several MTurk design choices, such as worker anonymity and isolation, are problematic in other environments. This paper introduces Frenzy, a platform for friendsourcing. Frenzy helps people who are closely connected in a community complete crowdsourcing tasks on a platform that affords more user control and freedom than traditional crowdsourcing platforms. Our evaluation of Frenzy shows that friendworkers can find meaningful work to do, effectively use discussion to reduce uncertainty, and finish the task. Most importantly, they are happy with the quality of the output and indicate a desire to use Frenzy for their own tasks such as: creating wedding albums, coding social science data, and creating sessions of accepted conference papers.